Liberalism and Community - Kautz, Steven (Cornell University Press, 2018)
Contemporary political theory has experienced a recent revival of an old idea: that of community. In Liberalism and Community, Steven Kautz explores the consequences of this renewed interest for liberal politics. Whereas communitarian critics argue that liberalism is both morally and politically deficient because it does not adequately account for equality and virtue, Kautz defends liberalism by presenting reports of various partisan quarrels among liberals (who love liberty), democrats (who love equality), and republicans (who love virtue). Founded on the classic texts of Locke and Montesquieu, the liberalism that Kautz advocates is cautious and conservative. He defends it against the arguments of important new communitarians-Richard Rorty, Michael Walzer, Benjamin Barber, and Michael Sandel-and contrasts communitarian and liberal views on key questions. He discusses Walzer' s account of moral reasoning in a democratic community, engages Barber on the nature and limits of republican community, and takes on Rorty's communitarian account of moral psychology and the nature of the self. Kautz also explores the concepts of virtue, tolerance, and patriotism-issues of particular interest to communitarians which pose special problems for liberal political theory-in an effort to rebuild a new and more tenable interpretation of liberal rationality.